LEGAL PROTECTION ON RIVER ECOSYSTEM TOWARDS ENVIRONMENTAL SUSTAINABILITY IN SAND MINING ACTIVITIES - Daulay, Nisrina Ramadhani (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2024)
Earth's natural resources, such as minerals and coal, are natural resources that cannot be renewed, so they must be managed optimally to achieve benefits and prosperity for the people. Mineral and coal mining activities have been regulated and stipulated in Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining and are based on legal principles. This journal discusses the protection of river ecosystems towards environmental sustainability in sand mining activities. The fact is that mining is still widespread, using an open-pit mining system, such as sand mining, which is mainly carried out by people's businesses and results in environmental damage. Most miners survive for their livelihood and hereditary business and ignore permits. This article aims to analyze the factors behind sand mining activities without permits. The impact of environmental damage and disruption of the river ecosystem due to sand mining and the efforts to overcome and protect the river ecosystem from a legal perspective will be analyzed. The method used is normative juridical, using legal materials in literature studies or secondary legal materials and related cases. The research results show various factors behind sand mining, positive and negative impacts, and mitigation efforts from a legal perspective with the critical role of the community.